Hat die Fehlallokation von Produktionsfaktoren zur Produktivitätsschwäche in Deutschland beigetragen? - Nils Jannsen (Zeitschrift für Wirtschaftspolitik, 2019)
Productivity growth in many advanced economies has decelerated in the last decades. There is increasing evidence that the misallocation of production function has contributed to the weakness in productivity. Factors behind this misallocation could include low interest rates or credit booms. In this paper, I evaluate the most recent findings on the impact of misallocation of production factors on productivity and assess their role for the weakness in productivity growth in Germany. Overall, the misallocation of production factors seem to have been less important in Germany than in other advanced economies. Behind the backdrop of the low interest environment has been in place for an extended period of time, the risks that productivity growth is damped due to the misallocation of production factors is increasing.
Keywords: D24; E44; O47; 330; Produktivität; Fehlallokation; Produktionsfaktoren; Finanzkrisen; Productivity; misallocation; production factors; financial crises